(untitled) (Al-Academy, 2024)
In recent years, the world has witnessed tremendous development in the field of artificial intelligence, and its impact has cast a shadow on human life in general and on those working in the field of graphic design in particular. According to expectations, artificial intelligence will become an integral part of our daily lives, and graphic design is one of the fields that has invested in the developments of artificial intelligence. It has become possible to apply artificial intelligence techniques to produce designs more accurately and effectively. Thanks to advanced algorithms and software, it has become possible to create innovative and attractive designs faster and easier than before. As well as analyzing user data and understanding their behaviors and preferences, which helps create interactive designs that better meet their needs. In creating customized designs that adapt to the user’s behavior and provide him with a unique personal experience, it seems that artificial intelligence has brought about a clear change in the field of graphic design, and from here the research problem emerged (what are the changes brought about by artificial intelligence in graphic design?) and the research aimed to know the future effects. The potential impact of artificial intelligence in graphic design. The study dealt with, within its theoretical framework, two main axes: the first (artificial intelligence, origins and development - advantages and disadvantages), and the second (the effectiveness of artificial intelligence in graphic design). The research adopted the descriptive approach and the content analysis method to analyze nine research samples to reach a number of results. The conclusions, including: 1. Artificial intelligence has the ability to classify different input data and use a certain part of the data as needed in the future. 2. AI tools in graphic design are unable to “think” independently as they are unable to assess the context in which the task should be performed